From Tradition to Innovation: Exploring the Impact of Seurunee Kalee Based Ethnoscience in Guided Inquiry Physics Learning - Elvida, Elvida; Lee, Mei Chi (Schrödinger: Journal of Physics Education, 2025)
Purpose of the study: This study aims to examine the effect of the guided inquiry learning model integrated with an ethnoscience approach using the Seurunee Kalee context on students’ critical thinking skills in learning sound waves at Dewantara 1 State Senior High School. Methodology: This study used a mixed-method approach with an explanatory sequential design and a quasi-experimental Non-Equivalent Control Group Design. Data were collected using tests, questionnaires, and interviews. Learning tools included worksheets and guidebooks. Data analysis employed SPSS version 25 for quantitative analysis and the Miles and Huberman model for qualitative review. Main Findings: The guided inquiry learning model integrated with an ethnoscience approach using the Seurunee Kalee significantly improved students’ critical thinking skills on sound waves. The experimental group’s mean score increased from 31.81 to 78.63, while the control group rose from 29.09 to 68.18. The t-test result (Sig. = 0.039 < 0.05) confirmed a significant difference. Student responses reached 86.79%, categorized as very strong. Novelty/Originality of this study: This study introduces the integration of a guided inquiry learning model with an ethnoscience approach using the Seurunee Kalee context in physics learning. The novelty lies in combining local cultural values with scientific inquiry to enhance students’ critical thinking skills, providing a new framework for contextualized and culturally relevant science education.